STUDY OF ASSOCIATION OF INFLAMMATORY MARKERS WITH METABOLIC SYNDROME IN PREDIABETIC PATIENTS AT TERTIARY CARE CENTER OF RAJASTHAN, INDIA - SHARMA, RITU; KANWAR, GULAB; MANGUKIYA, KETAN; PRAKASH SHARMA, CHANDRA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Background: Metabolic syndrome (MS) is associated with the risk of developing cardiovascular disease and type 2 diabetes mellitus. The preferred clinical approach to cardiovascular prevention is to treat all the metabolic risk factors. Objective: The objectives is study of acute-phase reactants in MS patients. Methods: This study was conducted on 250 subjects and controls at Government Medical College and Associated Group of Hospitals Kota, Rajasthan from October 2019 to September 2021. The study group had 125 MS cases and an equal number of healthy controls. Demographic characteristic of all participants noted including age, sex, weight, and height. Results: We observed a significant rise in blood glucose, total cholesterol, S. triglyceride, S. low-density lipoprotein (LDL). S. Very LDL S. C-reactive protein (CRP), and ferritin level in MS cases when compared to control subjects, while serum high-density lipoprotein level found to be decreased in MS patients as compared to control group. Conclusion: In this study, both CRP and ferritin level are increased as the number of components of MS increased. Therefore, these inflammation parameters could accurately and timely discriminate patients with MS, according to IDF criteria, who are at increased risk for future cardiovascular events. There was a significant correlation between inflammation and the diabetic complications.